Employment Adjustments in High-Trade-Exposed Manufacturing in Canada - Coulombe, Serge (Université d'Ottawa | University of Ottawa, 2008)
The study presents a model and estimates the dynamic response of employment in high-trade-exposed manufacturing to the Canadian dollar’s appreciation. The evolution of employment shares of high-trade-exposed manufacturing for the 10 provinces from 1987 to 2006 is captured using a general error correction model. This model is estimated using state-of-the-art timeseries–cross-sectional (TSCS) data econometrics. The main finding of the study is that a substantial part of the adjustment to the Canadian dollar’s appreciation since 2002 had already been completed in Canadian high-trade-exposed manufacturing industries by July 2007. However, simulation results suggest further employment losses in these industries if the value of the Canadian dollar remains around US$0.95. The reason for these further losses is that employment share does not adjust immediately to movements in the exchange rate. Estimates from the models indicate that between 60 percent and 70 percent of the adjustment to exchange rate movements is completed after two years. Consequently, most of the adjustment that still needs to be done results from the appreciation of the Canadian dollar thus far in 2007. The results also suggest that the effect of movements in the real exchange rate on employment in high-trade-exposed manufacturing is highly heterogeneous across provinces. Not surprisingly, the results suggest that the effect would be greater and particularly significant in Quebec and Ontario. If the dollar remains around US$0.95, simulation results suggest that the proportion of the adjustment that still needs to be done (July 2007) is less in Quebec (between 18 percent and 26 percent) and Ontario (between 27 percent and 33 percent) than in Canada as a whole (between 30 percent and 36 percent). If the Canadian dollar remains at or around parity with the U.S. dollar, the proportion of the adjustment still remaining increases to the 31 percent and 37 percent range for Quebec, 39 percent and 43 percent range for Ontario, and 42 percent and 46 percent range for Canada as a whole. There is a considerable amount of risk involved in simulation exercises of this type. The risks are related to uncertainty regarding the future evolution of two key variables of the models: the value of the Canadian dollar, and the evolution of the U.S. economy. Risk also results from model uncertainty. / On présente dans cette étude un modèle économétrique dynamique conçu pour mesurer l’incidence de l’appréciation du taux de change réel sur l’emploi dans l’industrie manufacturière exposée à la concurrence étrangère. Un modèle de correction d’erreurs est utilisé afin de rendre compte de l’évolution de la part de ce type d’emploi dans les dix provinces canadiennes de 1987 à 2006. Le principal résultat fondé sur les dernières données utilisées dans l’étude, soit celles de juillet 2007, est que l’ajustement de l’emploi à l’appréciation du taux de change depuis 2002 a déjà été opéré en grande partie. Cependant, les résultats de simulations donnent à penser que d’autres pertes d’emploi dans les industries manufacturières exposées à la concurrence étrangère sont à prévoir si le dollar canadien se maintient autour de 0,95 É.-U. Ces pertes supplémentaires s’expliqueraient par le fait que l’emploi ne s’ajuste pas instantanément aux fluctuations du taux de change. Selon le modèle, 60 à 70% de l’ajustement de l’emploi au taux de change est réalisé après 2 ans. Le gros de l’ajustement qui reste à faire découle de la forte appréciation du taux de change en 2007. Les résultats portent également à croire que les effets des variations du taux de change réel sur la part de l’emploi dans le secteur manufacturier exposé à la concurrence étrangère varient considérablement d’une province à l’autre. Les effets apparaissent beaucoup plus importants au Québec et en Ontario. De plus, si le dollar se maintient autour de 0,95 É.-U., les résultats donnent à penser que la part de l’ajustement qui resterait à être opéré (en juillet 2007) est inférieure au Québec (entre 18 et 26%) et en Ontario (entre 27 et 33%) par rapport à l’ensemble du Canada (entre 30 et 36%). Cependant, si le dollar se maintient autour de la parité, la part de l’ajustement qui reste à faire s’accroît et se situe dans une fourchette de 31 à 37% pour le Québec, de 39 à 43% pour l’Ontario, et de 42 à 46% pour l’ensemble du Canada. Le risque associé à des exercices de simulation de ce type est considérable en raison notamment de l’incertitude entachant les perspectives d’évolution du dollar canadien et de l’économie américaine, et de l’incertitude intrinsèque au modèle.
Keywords: Exchange rate; labor market adjustments; Dutch disease; Kiviet adjustment; Canadian provinces; Taux de change; ajustements du marché du travail; malaise hollandaise; ajustement de Kiviet; provinces canadiennes